Cross-cultural measurement equivalence of the Revised Conflict Tactics Scales (CTS2) Portuguese version used to identify violence within couples - Claudia Leite Moraes; Michael E. Reichenheim
Following a previous evaluation of concept, item and semantic equivalences, this paper assesses the measurement equivalence between a Portuguese version of Revised Conflict Tactics Scales (CTS2) and the original instrument conceived in English. The CTS2 has been widely used to tap violence between couples. An intra-observer reliability evaluation involved 165 replications carried out within a 24-48 hour period. Kappa point-estimates were above 0.75 for all scales except sexual coercion. The analysis of internal consistency concerned 768 subjects with complete sets of items. Kuder-Richardson-20 estimates ranged from 0.65 to 0.86. Results were similar to those found in the original instrument in English for the negotiation, psychological aggression and physical violence scales, yet not so for the sexual coercion and injury scales. Factor analysis identified factors with a recognizable correspondence to the underlying dimensions, although a few inconsistencies were detected. For the assessment of construct validity (n = 528) associations between the instrument's scales were evaluated, as well as the relationships between violence and putative underlying dimensions. Overall, the findings suggest that the version can be used in the Brazilian context, although further investigation should be carried out to unveil some important remaining issues.